Digitalisasi Sosialisasi Bimbingan Dan Konseling - Aziz, Yusef Abdul; Suherman, Uman; Setiawati, Setiawati (Jurnal Eksplorasi Bimbingan dan Konseling, 2024)
The digital era has begun marked by the rampant use of the internet and social media in every sector of individual life, be it economy, health, government, or education. Current education, especially in guidance and counseling, needs to adapt to the times to involve the internet and social media in guidance and counseling or can be called digitalization of guidance and counseling, especially in marketing or socialization of guidance and counseling. Researchers aim to obtain an overview of the socialization of guidance and counseling that occurs in Indonesia and provide alternatives for socialization of guidance and counseling in the digital era. The study uses a literature review approach, collecting and analyzing articles, journals, books, or other sources that are in accordance with the object of research.